The Effect of Communication Strategy Training on Limited English Proficiency Learners' Strategy Use, Fluency and Perception in an English for Occupational Purpose Programme - Megawati, Soekarno (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Communicative competence encompasses grammatical, sociolinguistic, discourse and strategic competence. This research focused on strategic competence, which is the ability to use communication strategies for interaction within the limits of linguistic competency. Communication strategies are compensatory strategies for overcoming gaps in linguistic deficiency as well as strategies for enhancing the negotiation of meaning. The purpose of this research was to investigate the effect of communication strategy training on limited English proficiency learners’ strategy use, fluency and perception in an English for Occupational Purpose programme. The objectives of this research were: 1) to examine the frequency of communication strategies used in technical presentations and dialogues before and after communication strategy training; 2) to measure the fluency of speech of the EOP learners in the preliminary and concluding technical dialogues in a communication strategy training; and 3) to study the learners’ perception of their use of communication strategies during the communication strategy training. The communication strategy training involving 23 limited English proficiency learners was carried out over 13 sessions, with each session focusing on a different communication strategy. The technical presentations and dialogues were recorded and transcribed for the analysis of the participants’ use of communication strategies and their fluency. The Oral Communication Strategies Inventory and strategy diary were used to study learners’ perception of their use of communication strategies. The analysis of the transcripts showed a reduction in the frequency of communication strategies used from 65.13 ptw to 51.43 ptw from the beginning to the end of the training, but an increase in the types of communication strategies used from 66.54 ptw to 71.20 ptw respectively. As for fluency, the C-Units showed that these limited proficiency English iv learners had improved their fluency with the range of 4.01 to 6.30 average C-Units. The OCSI results showed that the participants reported higher frequencies for most of the communication strategies taught during the communication strategy training. The analysis of the strategy diary showed that the participants’ awareness of communication strategies and confidence in using the language had increased during the training. The findings of this study suggested that the communication strategy training had enabled the participants to maximise the use of their existing linguistic resources and develop in their strategic competence.